2002
DOI: 10.1108/09555340210444211
|View full text |Cite
|
Sign up to set email alerts
|

Culture in defining consumer satisfaction in marketing

Abstract: The objectives of this article are to explain the importance of company culture and to point to the appropriateness of customer orientation as a method of expressing culture. The article further determines the connection between customer satisfaction and employee satisfaction and points to possible resistance when creating company culture through customer orientation. It further defines the relation between company mission and culture and explains the significance of researching value and researching customer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…For instance, in one study, Vranesevic, Vignali, and Vignali (2002) explained the importance of company culture and point to the appropriateness of customer orientation as a method of expressing culture. Based on this, it may be suggested that a different external measure of performance, such as customer satisfaction or growth, be used in future studies.…”
Section: Limitations and Direction For Future Researchmentioning
confidence: 98%
“…For instance, in one study, Vranesevic, Vignali, and Vignali (2002) explained the importance of company culture and point to the appropriateness of customer orientation as a method of expressing culture. Based on this, it may be suggested that a different external measure of performance, such as customer satisfaction or growth, be used in future studies.…”
Section: Limitations and Direction For Future Researchmentioning
confidence: 98%
“…Customer orientation (also known as market orientation or customer care) is considered by some authors to be an integral part of the overall organizational culture and to involve two dimensions: a) customer focus, an organization's understanding of customer needs, and b) needs assessment, the extent to which an organization monitors whether customer needs are being satisfied (Green, Chakrabarty & Whitten, 2007). Vranesevic et al (2002) state that companies with a customer orientation take into consideration the interests of their consumers in all their activities and that those interests are partners in achieving organizational success. Additionally, Parasuraman (1987) considers a customer-oriented organizational culture to be a prerequisite for organizations to develop a competitive advantage.…”
Section: The Influence Of Organizational Culture Type On Customer Orimentioning
confidence: 99%
“…Furthermore, it has been proposed that organizational culture may be more critical than formal written guidelines when it comes to adequately dealing with the service delivery processes, and that a customer oriented organizational culture could be crucial to the success of services marketing (Parasuraman, 1987;Sin & Tse, 2000;Vranesevic, Vignali, & Vignali, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Customer satisfaction leads to significant economic benefits for organisations, and by understanding customer satisfaction they can bring about what is considered a "strategic necessity" (Jaiswal and Niraj, 2011;Vranesevic, Vignali and Vignali, 2002). Satisfying customers is becoming more difficult as customers not only expect satisfaction based on functional benefits, but also seek satisfaction through unique experiences offered by organisations (McCole, 2004).…”
Section: Relationship Marketing Relationship Quality and Relationshimentioning
confidence: 99%